Novel Heterogenous CHS1 Mutations Identified in Five Japanese Patients with Chediak-Higashi Syndrome - Fuminori Tanabe; Hirotake Kasai; Michiko Morimoto; Shigeharu Oh; Hidetoshi Takada; Toshiro Hara; Masahiko Ito (Case Reports in Medicine)
Chediak-Higashi syndrome (CHS) is a rare, autosomal recessive disorder characterized by oculocutaneous albinism, recurrent bacterial infections and progressive neurological dysfunction. We demonstrate novel heterogenous mutations of CHS1, the responsive gene of CHS, identified in five Japanese patients with CHS. Patients 1, 2, and 3 were siblings, and they had albinism of the skin and hair. They all had a heterogenous two-base deletion (c.5541-5542 del AA, p.Q1847fsX1850) in exon 18. Patient 4 had a heterogenous single-base insertion (c.3944-3945 ins C, p.T1315fsX1331) in exon 10. The patient exhibited severe early-onset phenotype and suffered from hemophagocytic lymphohistiocytosis. Patient 5 had two heterogenous nonsense mutations; c.7982C>G, p.S2661X in exon 30 and c.8281A>T, p.R2761X in exon 31. The patient suffered from infections in childhood and had visual disturbance and albinism of the skin and hair. The CHS1 mutations described here have not been reported previously.